The Most Metal-rich Damped Lyα Systems at z ≳ 1.5 I: The Data. (4th January 2016) - Berg, Trystyn A. M.; Neeleman, Marcel; Prochaska, J. Xavier; Ellison, Sara L.; Wolfe, Arthur M.
Abstract: We present HIRES observations for 31 damped Lyα systems, selected on the basis of their large metal column densities from previous lower-resolution data. The measured metal column densities for Fe, Zn, S, Si, Cr, Mn, and Ni are provided for these 31 systems. Combined with previously observed large metal column density damped Lyα systems, we present a sample of 44 damped Lyα systems observed with high-resolution spectrographs ( R  ∼ 30, 000). These damped Lyα systems probe the most chemically evolved systems at redshifts greater than 1.5. We discuss the context of our sample with the general damped Lyα population, demonstrating that we are probing the top 10% of metal column densities with our sample. In a companion paper, we will present an analysis of the sample's elemental abundances in the context of galactic chemical enrichment.